ANALISIS PERAN KONFIRMASI PIUTANG DAN PENGENDALIAN INTERNAL DALAM MENJAMIN KEWAJARAN LAPORAN KEUANGAN - Ilham Muhammad Arfath; Muhammad Ersa Fahreza, Muh. Abdal Qaadiral Jailani S; Oni Tandilullu, Muh Arfandi Muin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the role of accounts receivable confirmation and internal control in ensuring the fairness of corporate financial statements. The main issue identified concerns the risk of inaccurate receivable presentation caused by weak internal control systems and ineffective receivable confirmation procedures. The purpose of this research is to analyze the extent to which receivable confirmation and internal control contribute to enhancing the reliability and fairness of financial information presented in financial statements. This study employs a qualitative descriptive method with a literature review approach. Data were obtained from relevant prior research articles, which were then analyzed and interpreted to draw conclusions from ten previous studies related to this topic. The analysis process involved identifying key findings, comparing results across studies, and determining the pattern of relationships between the effectiveness of receivable confirmation and internal control systems in ensuring the fairness of financial statements. The findings indicate that receivable confirmation plays a vital role as an independent verification tool to ensure the existence and accuracy of receivable balances. Strong internal control particularly in the aspects of segregation of duties, transaction authorization, and managerial supervision has been proven to reinforce confirmation results and reduce the risk of material misstatements. The synergy between both mechanisms enhances the reliability of information and ensures the fairness of financial reporting, thereby strengthening stakeholders’ trust in the integrity of corporate financial disclosures.